Master Plan Jakarta, Indonesia: The Giant Seawall and the need for structural treatment of municipal waste water. Issue 2 (30th September 2016) - van der Wulp, Simon A.; Dsikowitzky, Larissa; Hesse, Karl Jürgen; Schwarzbauer, Jan
Abstract: In order to take actions against the annual flooding in Jakarta, the construction of a Giant Seawall has been proposed in the Master Plan for National Capital Integrated Coastal Development. The seawall provides a combination of technical solutions against flooding, but these will heavily modify the mass transports in the near-coastal area of Jakarta Bay. This study presents numerical simulations of river flux of total nitrogen and N, N-diethyl- m -toluamide, a molecular tracer for municipal waste water for similar scenarios as described in the Master Plan. Model results demonstrate a strong accumulation of municipal wastes and nutrients in the planned reservoirs to extremely high levels which will result in drastic adverse eutrophication effects if the treatment of municipal waste water is not dealt with in the same priority as the construction of the Giant Seawall. Highlights: High relevance to the planned current developments of Jakarta Bay. Inclusion of scenarios with multiple end-members affecting Jakarta Bay and the Giant Seawall. First time application of DEET as molecular tracer for municipal waste water.